Histoplasmosis - An Unusual Cause of Spastic Paraplegia in an Immunocompetent Host in Bangladesh (Journal of Medicine, 2014)
A case of disseminated histoplasmosis in a 62-year immunocompetent healthy male presenting as compressive myelopahty without any pulmonary involvement or travel to endemic zone is described. The patient presented with fever, dull ache pain in the back of the lower chest, weakness of both lower limbs with impairment of emptying of bowel and bladder, physical findings include raised temperature, generalized lymphadenopathy, nontender mild hepatomegaly, spastic paraplegia with sensory level up to D8 and local tenderness over D7 vertebra without any gibbus. Diagnosis was confirmed by presence of histoplasmacapsulatum in the lymph node and soft tissue from the spine. The particular interest of this paper is to present a case of disseminated histoplasmosis especially presenting as spastic paraplegia in an immunocompetent host without pulmonary involvement and illustrates the importance of recognizing the possibility of histoplasmosis in Bangladesh where mimickers of histoplasmosis like tuberculosis is extremely common.DOI: http://dx.doi.org/10.3329/jom.v14i2.19688 J Medicine 2013, 14(2): 201-203